Properties of cellulose nanocrystals from oil palm trunk isolated by total chlorine free method - Junidah, Lamaming; Rokiah, Hashim; Leh, Cheu Peng; Othman, Sulaiman (Elsevier Science, Ltd., 2017)
Cellulose nanocrystals were isolated from oil palm trunk by total chlorine free method. The samples were either water pre-hydrolyzed or non-water pre-hydrolyzed, subjected to soda pulping, acidified and ozone bleached. Cellulose and cellulose nanocrystal (CNC) physical, chemical, thermal properties, and crystallinity index were investigated by composition analysis, scanning electron microscopy, transmission electron microscopy, fourier transform infrared, thermogravimetric analysis and X-ray diffraction. Water pre-hydrolysis reduced lignin (<0.5%) and increased holocellulose (99.6%) of ozone-bleached cellulose. Water pre-hydrolyzed cellulose exhibited surface fibrillation and peeling off after acid hydrolysis process compared to non-fibrillated of non-water pre-hydrolyzed cellulose. Water pre-hydrolysis improved final CNC crystallinity (up to 75%) compared to CNC without water pre-hydrolysis crystallinity (69%). Cellulose degradation was found to occur during ozone bleaching stage but CNC showed an increase in crystallinity after acid hydrolysis. Thus, oil palm trunk CNC can be potentially applied in pharmaceutical, food, medical and nanocomposites.